Collagenase as an effective tool for drug quantitation in tissues. (May 2015) - Qin, Ann Ran-Ran; Liang, Xiaorong; Deng, Yuzhong; Dean, Brian; Shahidi-Latham, Sheerin K
Background: In early drug-discovery research, traditional techniques to analyze drug concentrations in tissues for bioanalytical needs include bead beaters and probe homogenization devices, but are not as effective for tough fibrous tissues. To prepare these tissues, the enzyme collagenase was used to digest the collagen fibers present in epithelial and connective tissue.Results: The benefits of tissue homogenization using a bead beater following collagenase treatment of samples, as opposed to using bead beating alone, was investigated. Matrix effect, recovery factor and stability with and without collagenase were assessed.Conclusion: Little to no effects on the quality and reliability of collagenase treated samples were observed. This enzymatic approach is a feasible and effective tool for tissue homogenization and subsequent analysis by LC-MS/MS.